A invenção de Cabaceiras como cidade turística a partir da cultura do bode e das produções cinematográficas - Sales, Josélio dos Santos (2012)
Tourism as a social phenomenon has provided great cultural exchange, transforming territories, peoples and cultures. It is a phenomenon and increasingly complex, with political, economic, environmental, social and cultural. Locations in different parts of the world use this activity to disclose its natural beauty and cultural events, configuring it as tourist attraction sites. To understand these processes, our research investigated what were the elements that contributed to the invention of Cabaceiras in Cariri as tourist city from the culture of the goat and film production. The research was through descriptive and analytical studies with qualitative and quantitative approach. As methodological tool used direct observation and semi-structured interview applied to 16 residents of Cabaceiras. It was found that both the goat and the film served to generate a positive image of the city from the potential existing in the locality, but was not able to significantly transform the lives of people. There are, however, obstacles to be overcome: problems of infrastructure, the tourist flow increases only at the time of the "Festa do Bode Rei"; during the remainder of the year the city just hikers, who do not use neither the service nor the inn restoration of the city; cooperation among entrepreneurs, especially in the pursuit of sustainable development is still in its infancy, the support of government activity has decreased, although the official line is different.